Air-Leak Syndrome with Spontaneous Tension Pneumothorax and Pneumomediastinum Caused by Bleomycin-Induced Organizing Pneumonia. Issue 1 (30th December 2022) - Vanmarcke, Cedric; Steelandt, Thomas; Vliegen, Anne-Sophie
Teaching Point: The appearance of pneumatoceles in a patient with organizing pneumonia is an early sign of leak syndrome and is a significant finding as its rupture can lead to a life-threatening tension pneumothorax. Air leak syndrome (ALS), consisting of pneumothorax, subcutaneous emphysema and pneumomediastinum, is a rare complication of organizing pneumonia (OP). We report a case of a patient with bleomycin-induced OP who develops a tension pneumothorax due to a ruptured pneumatocele caused by ALS and correlate with histopathological analysis. This is the third case in the literature with these findings and the first with a tension pneumothorax.